New energy levels of the $latex 4s^{2}4p5s$, $latex 4s^ {2}4p4d$ and $latex 4s^ {2}4p5p$ configurations of the Kr v spectrum - Raineri, María Mónica (2002)
The spectrum of four times-ionized krypton (Kr v) has been observed in the 240-2500 Å wavelength range. Three of the four possible levels of the $latex 4s^{2}4p5s$ configuration and two of the three remaining energy level values for the $latex 4s^{2}4p4d$ configurations were determined. Nine of the ten possible levels for the $latex 4s^{2}4p5p$ configuration are also reported. The observed configurations were interpreted theoretically by means of Hartree-Fock relativistic calculations and a least squares fit of the energy parameters to the observed levels. 111 new classified lines are reported among the $latex 4s^{2}4p^{2}$, $latex4s^{2}4p5p$, $latex 4s4p^{3}$, $latex 4s^{2}4p5s$, and $latex 4s^{2}4p4d$ configurations.